Substrate stiffness regulated migration and angiogenesis potential of A549 cells and HUVECs. Issue 4 (27th October 2017) - Zhao, Dan; Xue, Changyue; Li, Qianshun; Liu, Mengting; Ma, Wenjuan; Zhou, Tengfei; Lin, Yunfeng
Abstract : Tumor tissue tends to stiffen during solid tumor progression. Substrate stiffness is known to alter cell behaviors, such as proliferation and migration, during which angiogenesis is requisite. Mono‐ and co‐culture systems of lung cancer cell line A549 and human umbilical vein endothelial cells (HUVECs), on polydimethylsiloxane substrates (PDMS) with varying stiffness, were used for investigating the effects of substrate stiffness on the migration and angiogenesis of lung cancer. The expressions of matrix metalloproteinases (MMPs) and angiogenesis‐related growth factors were up‐regulated with the increase of substrate stiffness, whereas that of tissue inhibitor of matrix metalloproteinase (TIMPs) were down‐regulated with increasing substrate stiffness. Our data not only suggested that stiff substrate may promote the migration and angiogenesis capacities of lung cancer, but also suggested that therapeutically targeting lung tumor stiffness or response of ECs to lung tumor stiffness may help reduce migration and angiogenesis of lung tumor. Abstract : Surface morphology of PDMS substrates and the distinctive morphological features of A549 cells cultured on PDMS substrates with varying stiffness.